Peripheral HMGB1-induced hyperalgesia in mice: Redox state-dependent distinct roles of RAGE and TLR4 - Daichi Yamasoba; Maho Tsubota; Risa Domoto; Fumiko Sekiguchi; Hiroyuki Nishikawa; Keyue Liu; Masahiro Nishibori; Hiroyasu Ishikura; Tetsushi Yamamoto; Atsushi Taga; Atsufumi Kawabata (Journal of Pharmacological Sciences, 2016)
Nuclear HMGB1 that contains 3 cysteine residues is acetylated and secreted to the extracellular space, promoting inflammation via multiple molecules such as RAGE and TLR4. We thus evaluated and characterized the redox state-dependent effects of peripheral HMGB1 on nociception. Intraplantar (i.pl.) administration of bovine thymus-derived HMGB1 (bt-HMGB1), all-thiol HMGB1 (at-HMGB1) or disulfide HMGB1 (ds-HMGB1) caused long-lasting mechanical hyperalgesia in mice. The hyperalgesia following i.pl. bt-HMGB1 or at-HMGB1 was attenuated by RAGE inhibitors, while the ds-HMGB1-induced hyperalgesia was abolished by a TLR4 antagonist. Thus, nociceptive processing by peripheral HMGB1 is considered dependent on its redox states.